Becoming Worthy Ancestors : Archive, public deliberation and identity in South Africa - Mangcu, Xolela, 1966- (Book collections on Project MUSE., 2011)
Why does it matter that nations should care for their archives, and that they should develop a sense of shared identity? And why should these processes take place in the public domain? How can nations possibly speak about a shared sense of identity in pluralistic societies where individuals and groups have multiple identities? And how can such conversations be given relevance in public discussions of reconciliation and development in South Africa? These are the issues that the Public Conversations lecture series-an initiative of the Constitution of Public Intellectual Life Project at Wits Univ.